Os refugiados em manifestos políticos presidenciais: entre silenciar e dar voz = Refugees in presidential political manifestos: between silencing and giving a voice - Pinto, Maria Alexandra Guedes (2020)
The crisis of migrants and refugees in 21st century Europe has created new disagreements on the old continent that pose difficult challenges for the construction of European identity. Al-ready classified as the most massive post-war humanitarian and migratory crisis, the reality of migrants and refugees has revealed a Europe unable to respond to the problem with a joint solu-tion. In addition to the humanitarian aspect, often of dramatic contours exploited by the media, the phenomenon is also a source of friction between the institutions and the Member states of EU, threatening to become the trigger for a European political crisis and a new balance of forces between States. Given the centrality it has gained, the refugee crisis may also be viewed as a means of pursuing strategic advantage by different political factions, which extract significant dividends for their territorialisation from the issue. Europeanist discourses of tolerance and ac-ceptance, based on the ideals of solidarity of the European project, coexist with extremist, xeno-phobic and anti-integration discourses. In the present reflection, we analyse how the electoral political discourse, of the textual genre political manifesto, encodes argumentatively the refugee question, focusing, for this purpose, four of the electoral manifestos of the candidates for the Portuguese presidential elections of 2016. Following the proposal of Adam (2001, pp. 40-41) for the characterisation of a genre (in semantic, compositional/structural, enunciative, pragmatic, stylistic and phraseological, metatextual, peritextual and material components), we confirm that there is unity and diversity in the analysed specimens. On the one hand, unity that enables rec-ognising the different texts as manifestations of the same genre; on the other hand, diversity that translates/produces effects in the ethè and discursive/political strategies of each candidate. The refugee crisis is precisely one of the topics whose management diverges substantially from manifesto to manifesto, revealing specific discursive and political strategies.